Persaudaraan Sesama Muslim - Maryana Sepiana; Uss Husni Hoer; Syifa Alawiyah; Muhammad Gani Mulya Perdana (Tilawah: Journal of Al-Qur'an Studies, 2025)
Brotherhood among Muslims is a fundamental concept in Islamic teachings based on values of unity, compassion, and mutual assistance. The Qur'an and hadith explicitly emphasize the importance of strong, harmonious, faith-based relationships among Muslims. In QS Al-Hujurat verse 10, Allah SWT states, "Indeed, the believers are brothers," indicating the obligation for Muslims to maintain unity and prioritize peace in social life. The hadith of Prophet Muhammad SAW also underscores the value of brotherhood as a part of faith, as he said, "None of you truly believes until he loves for his brother what he loves for himself." Furthermore, the hadith on supporting and protecting each other in times of hardship teaches that brotherhood is not merely a concept but is realized through concrete actions of mutual support and care. This study refers to the Al-Adab Al-Mufrad by Imam Bukhari, which focuses on manners in social relations, and the Lulu’ wal Marjan, which compiles authentic hadiths from Sahih Bukhari and Sahih Muslim. Through these two sources, this study explores the values of brotherhood, empathy, and solidarity that every Muslim must possess to build a harmonious society. The findings show that brotherhood in Islam has interrelated spiritual and social dimensions, where faith is manifested through compassion and responsibility toward fellow Muslims. This study is expected to serve as a reference for strengthening the values of brotherhood in the lives of Muslims to create a more peaceful, united, and just society.